2005
DOI: 10.1002/asna.200510413
|View full text |Cite
|
Sign up to set email alerts
|

QPO as the Rosetta Stone for understanding black hole accretion

Abstract: Quasi periodic oscillations (QPO) seen in the X-ray fluxes of individual neutron stars and black hole sources are one of most intriguing phenomena in today's astrophysics. The QPO nature is visibly determined by super-strong Einstein's gravity. I argue here that it also profoundly depends on the MRI turbulence in accretion flows. Understanding the QPO physics may therefore guide accretion theory out of its present state of confusion.Comment: 5 pages, 2 figure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 20 publications
4
36
0
Order By: Relevance
“…Nevertheless, the relationship between Ṁ and L outflow is still an open question(e.g., Beckmann & Shrader 2012), which we will continue to study in future work. We note that Abramowicz & Kluźniak (2001), Abramowicz (2005), and references therein suggested that QPOs ratiocould represent oscillations occurring at different radii in the inner disk, which is also consistent with our findings. In future work, we plan to explore the stable region to search for the Z-Mode, the Figure 20.…”
Section: Astrophysical Implications Of Qpos In Regions Of Instabilitysupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, the relationship between Ṁ and L outflow is still an open question(e.g., Beckmann & Shrader 2012), which we will continue to study in future work. We note that Abramowicz & Kluźniak (2001), Abramowicz (2005), and references therein suggested that QPOs ratiocould represent oscillations occurring at different radii in the inner disk, which is also consistent with our findings. In future work, we plan to explore the stable region to search for the Z-Mode, the Figure 20.…”
Section: Astrophysical Implications Of Qpos In Regions Of Instabilitysupporting
confidence: 93%
“…In this sense, we are reexamining the original Chakrabarti (1989)adiabatic accretion flow with isothermal shock instability problem, since this instability problem is still unresolved. We will briefly discuss the fundamental parameters that allow us to determine the diskshock structures, and we refer the readers to the previous series of papers by Le & Becker (2004, 2005 for further details.…”
Section: Introductionmentioning
confidence: 99%
“…This suggestion was developed by them and collaborators into the ''QPO resonance model.'' The model uses the theory of small nonlinear oscillations (e.g., Nayfeh & Mook 1979) and attempts to explain many observational properties of QPOs in X-ray binaries by deriving them directly from the differential equations that describe two weakly coupled, nonlinear oscillators (for more information, see the collection of reviews in Abramowicz [2005]), r þ (! r ) 2 r ¼ X r (r; ṙ; z; ż); z þ (!…”
Section: Introductionmentioning
confidence: 99%
“…Other alternative possible mechanisms for QPOs in blazars on IDV timescales can also have a disk origin or can arise from relativistic jets. The former class includes small epicyclic deviations in both radial and vertical directions from exact planar motions within a thin accretion disk (e.g., [141]) and trapped pulsational modes within a disk (e.g., [123,142]). Using the detailed explanation of [142], one can also get the BH mass of the blazar.…”
Section: Quasi Periodic Oscillations In Intra-day Time Series Multi-wmentioning
confidence: 99%